Planning, Implementation, and Evaluation of Project-Based Learning for Early Childhood in Indonesia: A Descriptive Qualitative Study - Sadaruddin; Syamsuardi; Hasmawaty; Usman (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2025)
This study aims to describe and critically analyze the planning, implementation, and evaluation of the Project-Based Learning (PjBL) model in Early Childhood Education (ECE), while also exploring the supporting and inhibiting factors and gathering strategic recommendations from teachers as frontline practitioners. Using a descriptive qualitative approach, data were collected through classroom observations, semi-structured interviews, and document analysis involving teachers from selected kindergartens implementing PjBL. The findings reveal that teachers generally understand PjBL as a project activity but struggle to differentiate it from conventional crafts or display projects. Their understanding of the pedagogical structure of PjBL remains limited, particularly regarding essential elements such as driving questions, inquiry-based exploration, and authentic assessment. Lesson plans are often based on available topics rather than emerging from children’s interests, and assessment strategies are rarely integrated from the beginning of the planning stage. Implementation tends to be teacher-directed, limiting children’s autonomy, problem-solving, and collaborative learning opportunities. However, children show increased enthusiasm and curiosity when given opportunities to explore, especially through outdoor and environmental projects. Supporting factors include institutional encouragement, parental involvement, and the use of culturally relevant contexts. Conversely, challenges such as time constraints, inadequate training, and limited resources hinder effective implementation. Teachers recommend continuous, practice-based training, collaborative and flexible lesson planning, integration of community resources, and development of assessment tools that evaluate creativity, communication, and collaboration. This study contributes to a better understanding of how PjBL can be meaningfully adapted in early childhood settings and provides practical insights for improving teacher professional development and curriculum design.